Metacognitive reflection and insight therapy: a mini-review of advances, challenges, and future directions - Wiesepape, Courtney N.; Leonhardt, Bethany L.; Hamm, Jay A.; Faith, Laura A. (Frontiers in Psychology, 2026)
Metacognitive Reflection and Insight Therapy (MERIT) is a significant development in psychotherapy for schizophrenia spectrum disorders, emphasizing meaning-making, self-understanding, and self-directed recovery. Grounded in the integrated model of metacognition, MERIT aims to help individuals form more complex and integrated understandings of themselves, others, and their community. Recent studies support its impact on metacognition, functioning, and recovery, though its flexible, process-based nature presents challenges for research standardization and widespread dissemination. This mini review summarizes MERIT’s theoretical foundations, empirical support, and clinical applications, while discussing current controversies and research gaps. We conclude by identifying future directions for expanding MERIT across diagnostic groups and furthering our understanding of metacognitive change as a mechanism of recovery.